Is there a wage curve for the highly educated? - Sanna-Mari Hynninen (University of Essex, Institute for Social and Economic Research (ISER), 2009)
The study examines how the job competition among the highly educated affects their wages in regional labour markets. We estimate individual-level wage curves separately for graduates and post-graduates and divide the job competition in unemployed and employed job search by level of education. The study does not find a wage curve for the highly educated in Finland. The results indicate that the dynamics of the market apparent in the increased employed job search creates more job opportunities for the graduates in the private sector, while declining the opportunities of both the graduates and the postgraduates in the municipality sector.
Keywords: 330